Analysis of Eu3+ Emission from Mg2TiO4 Nanoparticles by Judd-Ofelt Theory - Katarina Vuković; Mina Medić; Milica Sekulić; Miroslav D. Dramićanin (Advances in Condensed Matter Physics)
Eu3+ doped Mg2TiO4 (2 at% of Eu) nanoparticles which are 5 to 10 nm in diameter are prepared by Pechini-type polymerized complex route followed with the calcination in the temperature range from 400°C to 700°C. Emission spectra display characteristic D0→FJ   (J=0, 1, 2, 3, and 4) spin forbidden f-f electronic transitions of the Eu3+ ions with the most pronounced emission coming from D0→F2   transition and with the emission decays varying between 0.57 and 0.87 ms for samples prepared at different temperatures. Judd-Ofelt theoretical analysis of the emission spectra of Eu3+ ions was performed, which allowed calculating radiative and nonradiative emission probabilities, Judd-Ofelt intensity parameters, and the quantum efficiency of the Eu3+ emission in the Mg2TiO4 nanoparticles. The analyses showed the existence of high asymmetry around the metal ion sites. Also, the largest quantum efficiency of emission of 58.5% is found in nanoparticles prepared at 600°C.